Policies and Programs Affecting Land Management Practices, Input Use, and Productivity in the Highlands of Amhara Region, Ethiopia - Benin, Samuel (International Food Policy Research Institute, 2006)
Increasing agricultural productivity is an important challenge in Sub-Saharan Africa (SSA). Since the 1960s, agricultural production in SSA has failed to keep up with population growth. The situation is severe in Ethiopia, particularly in the highland areas, where agriculture is primarily rain fed (about 95 percent); soil loss rates average 21 to 42 tons per hectare per year on cultivated lands (Hurni 1988; Kebede 1996); many soils show large negative nutrient balances (Stoorvogel, Smaling, and Janssen 1993; Elias, Morse, and Belshaw 1998); cereal yields are less than 1 ton per hectare in many places; and up to 2 percent of total crop production is lost annually from soil erosion alone (Kappel 1996).